MARKETING COMMUNICATION PROGRAM DESIGN OF MAILO.LTD USING BENCHMARKING AND ANALYTICAL HIERARCHY PROCESS - Hafiza Aprilia; Agus Achmad Suhendra; Sari Wulandari (Sean Institute, 2021)
Mailo.ltd is one of the businesses engaged in the fashion sector that sells its main products like T-shirts and sweaters in Palembang City. Mailo.ltd sells its products offline and online. However, there are still sales gaps every month and the target is less than stable. The target of Mailo.ltd sales is unstable due to low awareness from the public because Mailo.ltd implement 6 out of 8 marketing communication mix that can still be optimized. Therefore, a research was conducted using the benchmarking method to identify mixed marketing communication gaps and the analytical hierarchy process (AHP) as a tool in finding best practices as a reference in benchmarking recommendations for improvement in mixed marketing communication. The priority order of marketing communication recommendations that need to be implemented by Mailo.ltd includes the use of google ads, maximizing website quality through optimizing the SEO value and bounce rate, posting frequency on Instagram, using e-mail blasts, SMS advertising, adding official resellers, conducting campaigns. social and humanitarian donations, organize our own events, hold giveaways, and use point of purchase in stores